Biosintesis nanopartikel perak (AgNP) menggunakan Bacillus firmus E65 dan aktivitasnya terhadap mikroba patogen - Yadi Suryadi; Dwi Ningsih Susilowati; I Made - Samudra (Agroindustrial Technology, University of Trunojoyo Madura, 2022)
Silver (Ag) in ionic form is toxic to microbial cells, but is environmentally friendly and safe for humans. This study aims to synthesize silver nanoparticles (AgNP) using Gram-positive bacterial isolate (B. firmus E65) as a bioreductor and to test its activity as an antimicrobial against Eschericia coli, Xanthomonas oryzae pv. oryzae (Xoo) and the fungus Colletotrichum gloeosporioides under in-vitro assays. AgNP was obtained by adding bacterial culture supernatant B. firmus E-65 to 5mM AgNO3 solution. The formation of AgNP was observed by changing the color of the solution after incubation at 37 °C for 72 hours. The UV-Vis spectrophotometer measurement to AgNP solution showed a maximum wavelength of 425 nm. The particle size of AgNP was 252.1 nm with intensity of 98.90 %. The result of bioassay against E. coli showed the greatest inhibition at 50 % AgNP (degree of inhibition (DI) =96.15 %), followed by 25 % AgNP (DI=76.92 %), and 12.5 % AgNP (DI=53.84 %). The bioassay against Xoo showed the greatest degree of inhibition was at AgNP 50 % (DI=92.85 %), followed by 25 % AgNP and 12.5 % AgNP (DI=85.71 %). Meanwhile bioassay against C.gloeosporioides, the greatest inhibition was observed at 25 % AgNP (DI=94.35 %), followed by 50 % AgNP (DI=91.9 %).